1999
DOI: 10.2337/diacare.22.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a prevention program for diabetic ketoacidosis in children. An 8-year study in schools and private practices.

Abstract: The prevention program for DKA in diabetic children aged 6-14 years, carried out in the Parma area during the last 8 years, was successful. Thanks to this program, cumulative frequency of DKA in new-onset IDDM decreased from 78% during 1987-1991 to 12.5% during 1991-1997. None of the newly diagnosed diabetic children aged 6-14 years and from the Parma area were ever admitted to the hospital for DKA after 1992.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
213
6
15

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(242 citation statements)
references
References 0 publications
8
213
6
15
Order By: Relevance
“…However, we did not observe a decrease in the frequency of mild or severe DKA at manifestation during the last 20 years. This is in contrast to reports from Finland [6] and Italy [9,10], where clear reductions in the frequency of DKA at diagnosis were reported. During the last 20 years in northern Finland, the prevalence of DKA has fallen from 29.5 to 18.9%.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, we did not observe a decrease in the frequency of mild or severe DKA at manifestation during the last 20 years. This is in contrast to reports from Finland [6] and Italy [9,10], where clear reductions in the frequency of DKA at diagnosis were reported. During the last 20 years in northern Finland, the prevalence of DKA has fallen from 29.5 to 18.9%.…”
Section: Discussioncontrasting
confidence: 99%
“…Some recent investigations have reported a decrease in DKA at onset [4,6,9], which may be due to an increase in medical awareness as a result of high background incidence [4,6], special information campaigns [9,10] or prevention programmes [6]. Because the incidence of childhood type 1 diabetes is increasing in most European countries [11] and numerous epidemiological publications have dealt with this increasing incidence, it might be expected that medical awareness in healthcare professionals should have improved in recent decades.…”
Section: Introductionmentioning
confidence: 99%
“…Shortening this latency period could be a winning preventive strategy. In the period of 1991-1997, we investigated this hypothesis in the province of Parma and demonstrated that, thanks to a school and physician campaign centered on the earliest symptom of diabetes (nocturnal enuresis in a "dry" child) as reported by 89% of parents, it was possible to prevent DKA (2). The key success of this campaign was due to a poster showing a child sleeping (potentially wetting the bed) as well as five attractive messages for parents: "Does your child drink and urinate more than usual?…”
mentioning
confidence: 99%
“…The recent literature on specific causes of mortality in diabetic youth also suggests that a large fraction of current deaths are related to acute diabetes complications and are therefore theoretically preventable. The demonstration by Vanelli et al (34) that a regional education program was able to reduce the occurrence of DKA dramatically is an example that may be relevant to this problem in the U.S. In conclusion, diabetes mortality in U.S. children appeared to plateau for the period 1984 -1998; further reductions in mortality may depend on overcoming the obstacles to earlier treatment of uncontrolled diabetes and/or prevention of ketoacidosis and hypoglycemia.…”
Section: Methodsmentioning
confidence: 99%